Pregnancy outcomes and maternal and perinatal complications of pregnancies following in vitro fertilization/intracytoplasmic sperm injection using own oocytes, donor oocytes, and vitrified embryos: A prospective follow-up study - Manish Banker; Vidhisha Mehta; Dipesh Sorathiya; Mira Dave; Sandeep Shah (Wolters Kluwer Medknow Publications, 2016)
Background: Several global studies have assessed maternal and perinatal outcomes and complications with the type of embryo transfer (ET) following in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI). The present study assessed the incidence of maternal and perinatal outcomes and complications following IVF/ICSI associated with the type of embryo transferred. Methodology: A total of 2112 ETs were performed in 2092 female patients aged 21-50 years between January 1 and December 31, 2014 (Group A: Fresh ET using self-oocytes: 691; Group B: Fresh ET using donor oocytes: 810; and Group C: Thaw ET using vitrified-warmed embryos: 611). Results: Incidence of clinical pregnancy rate, abortion rate, ectopic pregnancy rate, multiple pregnancy rate, live birth rate, and maternal complications was: Group A: 40.8%, 15.9%, 2.8%, 27.3%, 31.9%, and 17.7%; Group B: 50.2%, 21.8%, 1.6%, 32.5%, 36.9%, and 23.7%; and Group C: 42.9%, 25.2%, 1.1%, 31.3%, 29.6%, and 17.8%, respectively. Incidence of prematurity (<36 weeks of pregnancy), lower birth weight (<2500 g), perinatal mortality, and congenital abnormalities was as follows: Group A (29.52%, 36.2%, 5.22%, and 1.39%), Group B (42.58%, 46.2%, 4.6%, and 1.32%), and Group C (35.74%, 32.4%, 7.85%, and 0.94%), respectively. Conclusion: The higher incidence of the pregnancy outcomes in oocyte donation (OD) cycles can mainly be attributed to the younger age of oocyte donors. The higher incidence of complications in OD cycles could be due to advanced maternal age, different placentation, and immune tolerance.